2015
DOI: 10.1093/infdis/jiv431
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Local Pediatric Vaccination Rates and Patterns of Pneumococcal Disease in Adults

Abstract: Local variations in PCV uptake (and receipt of the booster dose) might influence the effectiveness of PCVs in preventing pneumococcal disease in adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 10 publications
3
6
0
Order By: Relevance
“…Therefore, direct protection of toddlers and preschool-aged children is the main causal driver of declines of IPD in adults, and carriage in infants <6 months old is either an intermediate step on the causal pathway or due to confounding, but is probably not the main causal driver (Figure S1). Such a mechanism is consistent with the delays in indirect protection observed in adults in several high-income populations following the introduction of PCV (15,27).…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…Therefore, direct protection of toddlers and preschool-aged children is the main causal driver of declines of IPD in adults, and carriage in infants <6 months old is either an intermediate step on the causal pathway or due to confounding, but is probably not the main causal driver (Figure S1). Such a mechanism is consistent with the delays in indirect protection observed in adults in several high-income populations following the introduction of PCV (15,27).…”
Section: Discussionsupporting
confidence: 80%
“…(27). Likewise, previous analyses demonstrated that the decline in IPD in adults in the US was delayed by ~1 year compared to the decline in IPD in children <5 years old (15). These patterns reinforce the notion that it is important to maintain strong immunity to colonization in these older children in order to maintain indirect protection of younger children and adults.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…For each ZIP code during each month/year, we estimated the number of children eligible to receive PCV7 and the number of children who received three and/or four doses using a cohort approach while assuming a constant birth rate over the year and that vaccinations for children who received three or four doses were administered according to schedule. 5,9 …”
Section: Methodsmentioning
confidence: 99%
“…This reduction was observed among children who received the vaccine and within the adult population, which was not vaccinated but which benefitted indirectly. 1-5 …”
Section: Introductionmentioning
confidence: 99%